Tapak Raja Cave as a Contextual Social Studies Learning ‎Resource for Strengthening Students’ Environmental ‎Awareness and Ecotheological Values - Suwarno Suwarno; Wisnu Wisnu; Jacky Jacky (Yayasan Darussalam Bengkulu, 2026)
This study aims to analyze the utilization of Tapak Raja Cave as a contextual Social Studies learning resource for strengthening students’ environmental awareness and ecotheological values at MTs Negeri 3 Penajam Paser Utara. The study employed a descriptive qualitative design supported by descriptive quantitative summaries involving 20 seventh-grade students. Data were collected through observation, student reflection sheets, semi-structured interviews, and documentation during a field-based learning activity at Tapak Raja Cave. The findings showed that cave-based Social Studies learning generated high positive affective responses among students, ranging from 90% to 100%. Students’ cognitive understanding reached 100%, internalization of ecotheological and character values reached 96.25%, evaluation of the learning process reached 91.9%, and open-ended reflection reached 94%. These findings indicate that Tapak Raja Cave can function as a contextual learning site that connects Social Studies concepts with environmental conservation, local community livelihoods, and religious ecological awareness. The study contributes to the development of local-potential-based Social Studies learning by demonstrating how a cave ecosystem can be pedagogically used to integrate environmental awareness and ecotheological value formation in madrasah education.